Enhanced Targeting, Retention, and Penetration of Amphotericin B Through a Biomimetic Strategy to Treat Against Vulvovaginal Candidiasis. Issue 1 (25th September 2022) - Lin, Yijing; Yin, Qingqing; Zhuge, Deli; Hu, Yiqin; Yang, Xuewei; Tian, Dongyan; Li, Li; Wang, Haonan; Liu, Shuangshuang; Weng, Cuiye; Zhang, Xufei; Wen, Bin; et al.
Abstract: An effective therapeutic strategy to treat vulvovaginal candidiasis (VVC) that is mainly caused by Candida albicans ( C. albicans ) infection is highly desirable. While Amphotericin B (AmB) has demonstrated promise, its precise localization to C. albicans burden at vaginal sites is oftentimes limited by the high fluidity microenvironment of the vagina, which can compromise treatment efficacy. To overcome this issue, a biomimetic AmB delivery system is developed, in which AmB preloaded polymeric cores are cloaked with vaginal epithelial cells membrane (VM‐ANP). With its cell membrane coating, VM‐ANP naturally targets and strongly binds with C. albicans, thus resisting the self‐cleaning of vaginal fluid. Besides its long retention property, VM‐ANP could penetrate deeply in vaginal tissue to achieve its full antifungal potential by attaching to hidden C. albicans . It is shown that both C. albicans suspension and biofilm biomass could be effectively inhibited by the VM‐ANP in vitro. In a C. albicans intravaginal infection model, treatment with VM‐ANP results in significantly decreased fungal challenges both in vaginal tissue and fluid. Overall, such biomimetic strategy adds the merit of natural cell membrane into the targeted delivery of drug in treating VVC, which also serves as a promising platform against vaginitis‐related pathogens. Abstract : Amphotericin B (AmB) preloaded polymeric cores cloaked with vaginal epithelial cells membrane (VM‐ANP) are capable of localizing and penetrating to the sites of Candida albicans infection. Upon such strong adhesion, retention, and penetration, VM‐ANP shows a controlled release of AmB; thus, enhancing the fungal killing to reach its full potential without significant side effects.